Defesa antioxidante de crianças e adolescentes com dermatite atópica - Andrade, Roseani Da Silva [UNIFESP] (2019)
Introduction: An atopic dermatitis (AD) is a recurrent chronic cutaneous inflammatory disease, usually starting in early childhood. It is possible to register a spontaneous form after puberty in some patients. Oxidative stress is an imbalance between reactive species production and antioxidant defense; promotes tissue inflammation by the positive application of genes coding as inflammatory cytokines. Oxidative stress may play a pathogenic role in AD, since inflammatory cells release free radicals when activated. Objectives: To compare the antioxidant defense of children and adolescents with AD with their symptoms and to verify the association of antioxidant defense with disease severity and nutritional status. Methods: Through a cross-sectional, prospective and observational study, evaluated 48 children and adolescents with AD and 25 controls on nutritional status (ZIMC / I, ZE / I) and biochemical analysis of substances A, C, E and D. , zinc (Zn), copper (Cu), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), ultra-sensitive C-reactive protein (PCRus), interleukin 33 (IL33) and lipid profile. Results: the average age of the groups was 10 years; Eleven (22.9%) individuals in the AD group had obesity, as well as higher ZIMC / I score (p = 0.04). There was a significant difference between AD group users (98.3 ± 21.4 vs 76.9 ± 16.1; p <0.001). As ratios vitamin E / cholesterol (p = 0.018), vitamin E / triglycerides (p = 0.010) and vitamin E / total lipids (p = 0.013) were significantly lower in the group with moderate / severe AD. In the multivariate analysis, the variables ZE / I (p = 0.026) and Zn (p = 0.003) were significant for the AD group, which presented lower ZE / I score and higher Zn levels. There was a significant negative correlation between the Atopic Dermatitis (SCORAD) score and vitamin E samples. Conclusion: Children and adolescents with AD, mostly moderate / severe, overweight, overweight, central adiposity, shorter stature and lower amount of serum zinc. There was a negative correlation between vitamins E and D with gravity suggesting a possible role of these vitamins in the treatment of children and adolescents with AD.